IMPLEMENTATION OF WEBSITES AS MEDIA IN INCREASING STUDENTS’ INTEREST AND STUDY RESULT IN ENGLISH VOCABULARIES (Conducted At SD Lab. Kota Gorontalo In Fifth Grade) - Nurlaela (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tompotika Luwuk, 2018)
In the learning process, students usually never pay attention to the teacher, and finally can influence their study result. It is happen because of the students feel bored and not interest to study English, especially English vocabularies. This research used website as a learning media. The objective of this research is to know whether website can increasing students’ interest in English vocabulary and can influence the students’ study result or not. In that case, the sample of this research is fifth grade of SD Lab Kota Gorontalo which consists of 17 students. The method of this research is quasi experimental method which used pretest and posttest design. The instrument which is used in collecting the data is the test, and it was analyzed by using t-test. The result of this research shows that the using of website can increase students’ interest and can influence students’ achievement. The criteria used to verify the hypothesis is the is accepted if is smaller than ( < ). Based on the analysis of this research, it is found that is smaller than (-4 < 2.037) with the level of significance α=0.05 and dk=(n1+n2-2). It means that the hypothesis is acceptable. In the other word, it found that website can increase students’ interest in English vocabulary and can influence students’ study result.